Functional expression of chloride channels and their roles in the cell cycle and cell proliferation in highly differentiated nasopharyngeal carcinoma cells. Issue 9 (11th September 2014) - Huang, Weiyuan; Liu, Mei; Zhu, Linyan; Liu, Shanwen; Luo, Hai; Ma, Lianshun; Wang, Haibo; Lu, Ruiling; Sun, Xiaoxue; Chen, Lixin; Wang, Liwei
Abstract We previously demonstrated that the growth of the poorly differentiated nasopharyngeal carcinoma cells (CNE‐2Z) was more dependent on the activities of volume‐activated chloride channels than that of the normal nasopharyngeal epithelial cells (NP69‐SV40T). However, the activities and roles of such volume‐activated chloride channels in highly differentiated nasopharyngeal carcinoma cells (CNE‐1) are not clarified. In this study, it was found that a volume‐activated chloride current and a regulatory volume decrease (RVD) were induced by 47% hypotonic challenges. The current density and the capacity of RVD in the highly differentiated CNE‐1 cells were lower than those in the poorly differentiated CNE‐2Z cells, and higher than those in the normal cells (NP69‐SV40T). The chloride channel blockers, 5‐nitro‐2‐(3‐phenylpropylamino) benzoic acid (NPPB) and tamoxifen inhibited the current and RVD. Depletion of intracellular Cl− abolished the RVD. The chloride channel blockers reversibly inhibited cell proliferation in a concentration‐ and time‐dependent manner, and arrested cells at the G0/G1 phases, but did not change cell viability. The sensitivity of the three cell lines to the chloride channel blockers was different, with the highest in poorly differentiated cells (CNE‐2Z) and the lowest in the normal cells (NP69‐SV40T). ClC‐3 proteins were expressed in the three cells and distributed inside the cells as well as on the cell membrane. In conclusion, the highly differentiated nasopharyngeal carcinoma CNE‐1 cells functionally expressed the volume‐activated chloride channels, which may play important roles in controlling cell proliferation through modulating the cell cycle, and may be associated with cell differentiation. Chloride channels may be a potential target of anticancer therapy.